2016
DOI: 10.1177/1934578x1601100431
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Chemical Composition and Headspace Volatiles Profile of Achillea coarctata from Serbia

Abstract: This study reports the essential oil composition and headspace volatiles profile of Achillea coarctata Poir. from Serbia. The inflorescences, stems and leaves, and the aerial parts of A. coarctata were analyzed separately. Germacrene D, α-terpineol and 1,8-cineole were the main constituents of the aerial parts essential oil; 1,8-cineole, cis-cadin-4-en-7-ol and α-terpineol were the most dominant compounds in the inflorescence essential oil, while the most abundant components in the stem and leaf oil were germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Cis-cadin-4-ene-7-ol (5.32%), which also contribute a major proportion of essential oil of E. diffusum, was previously suggested responsible for the antimicrobial activity 35,36 . This oxygenated bicyclic sesquiterpene has also been reported from some angiosperms, Neolitsea kedahense-7.7% 36 , Achillea coarctata 37 , but this is the first report from pteridophyte. Kanchanapoom et al, studied the chemical composition of the aerial portion of E. diffusum growing in Thailand, by using 1 H-NMR and 13 C-NMR and four compounds, sammangaoside A, kaempferol 3-O-sophoroside, L-tryptophan and (3S, 5R, 6S, 7E, 9S)-megastigman-7-ene-5,6epoxy-3,9-diol 3-O-b -D-glucopyranoside were identified 38 .…”
Section: Fig 1: Gc-ms Chromatogram Of Essential Oil Of E Diffusumsupporting
confidence: 61%
“…Cis-cadin-4-ene-7-ol (5.32%), which also contribute a major proportion of essential oil of E. diffusum, was previously suggested responsible for the antimicrobial activity 35,36 . This oxygenated bicyclic sesquiterpene has also been reported from some angiosperms, Neolitsea kedahense-7.7% 36 , Achillea coarctata 37 , but this is the first report from pteridophyte. Kanchanapoom et al, studied the chemical composition of the aerial portion of E. diffusum growing in Thailand, by using 1 H-NMR and 13 C-NMR and four compounds, sammangaoside A, kaempferol 3-O-sophoroside, L-tryptophan and (3S, 5R, 6S, 7E, 9S)-megastigman-7-ene-5,6epoxy-3,9-diol 3-O-b -D-glucopyranoside were identified 38 .…”
Section: Fig 1: Gc-ms Chromatogram Of Essential Oil Of E Diffusumsupporting
confidence: 61%
“…from Trgovište, Serbia, with germacrene D as the main constituent of the aerial parts and stem and leaf essential oil, while the most dominant compound in the inflorescence essential oil was 1,8-cineole. [19] If we compare our results with previously published results regarding the chemical composition of the essential oils obtained from the same plant species, it is obviously that different factors (such as type of substrate, different climate conditions, different plant organs that were used for hydrodistillation as well as either the essential oil was obtained from fresh or airdried plant material) affect the qualitative and quantitative chemical composition of essential oils.…”
Section: Chemical Compositionmentioning
confidence: 66%
“…As mentioned, there are few reports regarding A. coarctata essential oils. [12][13][14][15][16][17][18][19] When we look at previous studies on A. coarctata from Turkey, viridiflorol, camphor and 1,8-cineole were reported as major constituents in essential oil obtained from this species by several authors. [12 -16] On the other hand, a literature survey revealed that essential oils of A. coarctata from Greece (inflorescence and leaves) was also dominated by oxygenated monoterpenes, 1,8-cineole and camphor.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Even though headspace G-C is extensively used a limited number of papers is focused on the analysis of headspace volatiles obtained directly from the plant material under static conditions. [4][5][6][7][8][9][10][11] More papers are related to HS-SPME analysis some of which refer to A. scoparia 12 and A. annua. [13][14][15][16][17] Static headspace analysis of plants is a very fast and inexpensive method.…”
Section: Introductionmentioning
confidence: 99%